Rapid Construction of Virtual Scenes for Large-Scale Crops Distribution. Issue 17 (2018) - Cheng, Chunming; Li, Jiayao; Zhou, Jianghui; Kang, Li; Sun, Ruizhi; Li, Guoliang
Abstract: With the development of computer hardware and virtual reality technology and its head-mounted display (HMD), the scale of the virtual environment that it can simulate is also growing, and related fields include forest simulation, virtual agriculture simulation and so on. However, it is urgent to solve the problem of slow construction speed of the scenes which include different kinds of three-dimensional models in the engineering practice. Aiming at the problem of crops planting by blocks in regular regions, a virtual scene construction method based on improved K-means clustering algorithm is proposed. For crops planting problems in irregular regions, we adapt the idea of visually adjusting the key points in regional boundaries to determine the region of planting crops in the virtual environment, proposing a rapid construction method of virtual scene based on Catmull-Rom Spline and Even-Odd Algorithm.